Barriers to accessing mental health services among university students: A systematic review - Kus Hanna Rahmi; Zakiyah Jamaluddin; Mahathir Yahaya; Azlini Binti Chik; Meiti Subardhini; Enung Huripah; Adi Fahrudin (Environment and Social Psychology, 2025)
Background: University students worldwide face escalating mental health challenges, yet their access to appropriate psychological support services remains critically limited. Despite growing institutional awareness of student well-being needs, systematic barriers continue to impede effective service utilization, creating a concerning gap between mental health needs and actual service engagement. Objective: This systematic review aims to comprehensively identify and analyze the multifaceted barriers that prevent university students from accessing mental health services, while simultaneously evaluating the effectiveness of interventions designed to address these obstacles. Methods: Following PRISMA guidelines [1] We conducted an extensive systematic review by searching seven electronic databases, including PubMed, PsycINFO, ERIC, CINAHL, Web of Science, Scopus, and the Cochrane Library for studies published between January 2017 and December 2024. We included empirical studies examining barriers to accessing mental health services among university students aged 18-30 years. Study quality was rigorously assessed using the Mixed Methods Appraisal Tool [2] and Newcastle-Ottawa Scale [3]. Data synthesis employed structured narrative analysis complemented by quantitative analysis where appropriate. Results: Our comprehensive search identified 2,847 initial records, from which 45 studies meeting strict inclusion criteria were analyzed, encompassing 78,392 participants across 23 countries. Through systematic analysis, three primary barrier categories emerged: individual-level barriers, including stigma, misconceptions, and help-seeking reluctance; structural barriers, encompassing financial constraints, service availability, and accessibility issues; and institutional barriers, involving inadequate resources, insufficient staff training, and system integration failures. Financial constraints emerged as the most frequently reported barrier across 69% of studies, followed closely by stigma-related concerns in 64% of studies and limited-service awareness in 58% of included research. Analysis of intervention studies revealed moderate effectiveness for comprehensive, multi-component approaches that address barriers at multiple levels simultaneously. Conclusions: Multiple interconnected barriers create complex obstacles to university students' access to mental health services. The evidence strongly supports implementing multi-level interventions that simultaneously address individual, structural, and institutional factors rather than targeting isolated barriers. Future research should prioritize implementation science approaches and examine the long-term sustainability of barrier-reduction interventions in diverse university settings.